Pengaruh Citra Destinasi, Kualitas Layanan, dan Nilai yang Dipersepsikan terhadap Loyalitas Wisatawan Nusantara pada Koridor Wisata Makassar–Toraja - Rahmat Rafi Al Ghifari; Nur Putri Sari Gassing; Tri Aguwinanda Sakti; Sulkah Baary Ramdani; Yudha Ari Wijaya (Ma Chung Press, 2026)
This study aims to analyze the influence of destination image, service quality, and perceived value on tourist satisfaction and loyalty among domestic tourists in the Makassar–Toraja tourism corridor. Tourist satisfaction is positioned as a mediating variable within the proposed structural model. Data were collected through a survey of 418 domestic tourists from Makassar who had previously visited Toraja. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that destination image, service quality, and perceived value have significant positive effects on tourist satisfaction. Additionally, these three variables also have significant direct effects on tourist loyalty. However, tourist satisfaction does not significantly influence loyalty and does not mediate the relationship between the antecedent variables and loyalty. Among the predictors, perceived value demonstrates the strongest direct effect on loyalty. These results indicate that tourist loyalty in the Makassar–Toraja tourism corridor is primarily driven by cognitive evaluations of value, service quality, and destination image rather than satisfaction alone. The study contributes theoretically by simultaneously testing direct and indirect relationships within an integrated model and offers practical implications for destination managers to prioritize strengthening the value proposition to enhance tourist loyalty.